The Influence of Cash and Receivables Management on Liquidity in Trading Companies in Makassar Central Market: JEL Classification: G31, G32, G51, L25, M21, O16 - Abbas, Muhammad (Journal La Bisecoman, 2025)
The research examines the effects of cash flow management and receivables control on business liquidity at trading companies within Makassar Central Market. The research investigates how operational cash flow management together with receivable processes support financial reliability when informal credit systems exist in conjunction with restricted formal financial institution services. The researchers conducted quantitative surveys with 100 market trading companies to apply regression analysis on cash and receivables management effects on liquidity levels. Liquidity enhancement arises from effective cash management and especially from receivables management according to research findings. Businesses can decrease their reliance on outside financing sources while satisfying short-term debts by handling receivables effectively in order to receive cash flow improvements in a timely manner. The analysis identifies the necessity for financial management systems which fit specific situations encountered in informal markets that lack traditional accounting systems. The research contributes useful knowledge about liquidity management in small enterprises while providing valuable advice to trading companies which aim to develop their financial management methods. The study outlines prospective recommendations for improving market trader financial skills while expanding their access to official financial products.